IMPROVING TEACHER QUALITY IN THE IMPLEMENTATION OF THE MERDEKA CURRICULUM: A QUALITATIVE CASE STUDY - Yandri Reasoa; Lisye Salamor; Herpie Lambiombir (CV. TOTUS TUUS, 2026)
This study examines how teacher quality is improved in the implementation of the Merdeka Curriculum at SMA Negeri 42 Central Maluku, Indonesia. The study was motivated by the strategic role of teachers in translating curriculum reform into meaningful, differentiated, and student-centered learning, particularly in schools that face contextual limitations related to infrastructure, digital access, and teacher readiness. A descriptive qualitative case-study design was employed. The research participants were selected purposively and consisted of the principal and the vice principal for curriculum, both of whom were directly involved in curriculum implementation and teacher development programs. Data were collected through observation, semi-structured interviews, and documentation, and were analyzed through data reduction, data display, and conclusion drawing. The findings reveal four interconnected dimensions of teacher-quality improvement. First, pedagogical competence was strengthened through in-house training, Merdeka Curriculum workshops, peer observation, learning communities, and training in the preparation of learning outcomes, learning objectives, teaching modules, and formative assessments. Second, personality competence was developed through stress-management webinars, emotional and spiritual intelligence training, coaching, and follow-up action plans designed to strengthen teachers as role models for character education and the Pancasila Student Profile. Third, social competence was enhanced through positive-culture workshops, collaborative reflection, and communication-oriented activities that supported inclusive learning relationships. Fourth, professional competence was improved through teacher working groups, direct practice, contextual adaptation, and the development of innovative teaching materials. The study concludes that teacher-quality improvement in the Merdeka Curriculum requires an integrated, school-based professional development model that combines technical training, reflective coaching, collegial collaboration, and contextual problem solving.